Public Library and Librarian Stereotypes in The Indonesian Film Kambodja - Nina Mayesti (Fakultas Adab dan Humaniora, UIN Syarif Hidayatullah Jakarta, Indonesia, 2023)
PurposeThis study aimed to describe the portrayals of a library and librarian in the Indonesian film Kam-bodja based on the suitability of historical facts and cultural aspects and to find out public per-ceptions and stereotypes about the image of librarians.MethodThis qualitative research study used a critical discourse analysis and the dispositive method to-wards the unit of analysis in the form of dialogues and film scene cuts. Data were obtained by watching, selecting dialogues and scenes, and making notes.Results/FindingsIt finds a portrayal of the public library, its operational activities, and worker according to the period 1955-1965 in the film. There are three representations of public libraries found in the film: a library as an information centre, a social place, and a quiet place. There are also three portray-als of librarian in the film: librarian is a female profession, has dominating power over library users, and is quiet and unapproachable.ConclusionThe representations of libraries and librarians in the film show consistency and sustainability in how the media represents libraries and the librarianship profession, which influences public per-ception. Such knowledge continuously reinforced through the media shows that the public still needs to familiarize themselves with libraries and librarianship. The negative image in various media is a challenge that must be faced for the sustainability of this field and is expected to reflect how the public views libraries and their profession.